КОНЦЕПЦИЯ ХОЗЯЙСТВЕННО-ПРАВОВОГО ОБЕСПЕЧЕНИЯ РЕСТРУКТУРИЗАЦИИ АКТИВОВ В УСЛОВИЯХ ДЕОФФШОРИЗАЦИИ - ГРИНЬКО, Алла Андреевна (SUPREMANCE OF LAW, 2016)
The article is devoted to the conceptual foundations of the economic and legal support of restructuring of business entities’ assets, justification and development of practical recommendations on the state regulation processes ofrestructuring of business entities’ assets in the current deoffshorization conditions. Considered theoretical and legal foundations of attracting by business entities offshore jurisdictions on the basis of legal arguments in the current economic conditions of Ukraine. Highlighted negative and positive features inherent to “offshore business”. Reveals the essence and content of the “restructuring” category. Structured modern system of legal support of restructuring of business entities of state and non-state sector of the economy which is determined by the system of sources of law, as well as structured organizational and legal measures for restructuring. Presented the he analysis of legislative initiatives concerning the ordering of relations of business entities with a foreign element of offshore jurisdictions. Presented the main stages of the formation of offshore Ukrainian legislation and its classifi cation. Marked and grouped ways to improve the effectiveness of the restructuring processes in the current economic conditions. The hypothesis of the present research is the assumption that the economic and legal support ofrestructuring processes of business entities’ assets in the deoffshorization conditions as well as the conclusions and proposals made on the basis of identification and analysis of features, trends and patterns of state regulation ofrestructuring processes of business entities ’ assets in the conditions of deoffshorization of Economy of Ukraine and It makes it possible to improve the state regulation of these processes.